Systemic Racism : Making Liberty, Justice, and Democracy Real - Thompson-Miller, Ruth; Ducey, Kimberley (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
This volume identifies some of the remaining gaps in extant theories of systemic racism, and in doing so, illuminates paths forward. The contributors explore topics such as the enduring hyper-criminalization of blackness, the application of the white racial frame, and important counter-frames developed by people of color. They also assess how African Americans and other Americans of color understand the challenges they face in white-dominated environments. Additionally, the book includes analyses of digitally constructed blackness on social media as well as case studies of systemic racism within and beyond U.S. borders. This research is presented in honor of Kimberley Ducey's and Ruth Thompson-Miller's teacher, mentor, and friend: Joe R. Feagin.
Keywords: Social sciences.; Social structure.; Social inequality.; Social sciences -- Philosophy.; elektronické knihy; electronic books